Begonia dicressine (Begoniaceae): a new record for India - Dipankar Borah; Momang Taram; Eric Wahlsteen (Nature Conservation Research: Заповедная наука, 2021)
Begonia, belonging to the family Begoniaceae, is one of the largest Angiosperm genera with a pan-tropical distribution. Northeastern India shows a high degree of endemism with several endemic species described from the region. Begonia dicressine, so far known from Myanmar, has been recorded for the first time in India from Namdapha National Park. Hence, the present record makes the westernmost distribution of the species and a new record for the flora of India.